2018
DOI: 10.3389/fphys.2018.01835
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Blood Parameters, Red Blood Cell Deformability and Circulating Nitric Oxide Between Males and Females Considering Hormonal Contraception: A Longitudinal Gender Study

Abstract: Red blood cell (RBC) deformability is an important determinant of the microcirculation. It is influenced by various hematological parameters but also by nitric oxide (NO) which is produced in RBC from L-arginine by RBC-NO synthase. Longitudinal studies on blood profile, deformability at rest and NO levels but also differences between males and females (±hormonal contraception; HC) are less known so far. The study thus aimed to investigate RBC deformability, RBC NO species (nitrite, RxNO), RBC L-arginine concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 40 publications
7
54
3
2
Order By: Relevance
“…The relatively small sample size of our study did not allow us to evaluate the impact of sex on the different parameters analyzed. Previous studies have reported sex differences in hematological parameters with higher RBC count, hematocrit, and hemoglobin concentration in males than in females [ 40 , 41 ]. Grau et al [ 40 ] also described that RBC deformability was higher in females not taking hormonal contraception (HC) compared to women taking hormonal contraception and compared to males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively small sample size of our study did not allow us to evaluate the impact of sex on the different parameters analyzed. Previous studies have reported sex differences in hematological parameters with higher RBC count, hematocrit, and hemoglobin concentration in males than in females [ 40 , 41 ]. Grau et al [ 40 ] also described that RBC deformability was higher in females not taking hormonal contraception (HC) compared to women taking hormonal contraception and compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported sex differences in hematological parameters with higher RBC count, hematocrit, and hemoglobin concentration in males than in females [ 40 , 41 ]. Grau et al [ 40 ] also described that RBC deformability was higher in females not taking hormonal contraception (HC) compared to women taking hormonal contraception and compared to males. Further studies are needed to test the sex differences on the hematological and RBC responses during such long-distance races.…”
Section: Discussionmentioning
confidence: 99%
“…Na posição em pé, a ausência de mecanismos reguladores permitiria o preenchimento dos vasos dos pés entre 300 e 800 ml, correspondendo ao deslocamento gravitacional do sangue, de modo que, em indivíduos saudáveis, esse é um fenômeno preventivo [20]. investigation comparing blood red cell passage values in the upper limb antecubital region, the authors identified higher values for men compared with women [26]. However, other studies on microcirculation did not find differences between genders [27], so further studies seem to be necessary to compare responses among healthy individuals with different physiological characteristics.…”
Section: Resultsunclassified
“…The authors declare that there is no financial or personal relationship that might be perceived as posing a potential conflict of interest [26]. No entanto, outros estudos sobre a microcirculação não encontraram diferenças entre os gêneros [27], portanto, estudos adicionais parecem ser necessários para comparar as respostas entre indivíduos saudáveis com diferentes características fisiológicas.…”
Section: Conflict Of Interestunclassified
“…While reduced deformability appears to be characteristic of healthy ageing, changes in circulating sex hormones in young versus post-menopausal women may be critical to erythrocyte function. Grau et al (2018) recently investigated the effects of fluctuating plasma oestrogen levels across the menstrual cycle on various haematological factors, including erythrocyte deformability. They present novel evidence that circulating oestrogen enhances erythrocyte deformability.…”
Section: The Erythrocyte In Sympatholysismentioning
confidence: 99%